Top answers

Maths
A Level

How do I differentiate (e^(2x)+1)^3?

You might be tempted to start by expanding the brackets, but in this case it's much easier to use the chain rule. This is the rule that, to differentiate f(g(x)), we find f'(g(x))*g'(x). In other words, t...

Answered by Alfie H. Maths tutor
3324 Views

It is given that n satisfies the equation 2*log(n) - log(5*n - 24) = log(4). Show that n^2 - 20*n + 96 = 0.

Given 2logan - loga(5n-24) = loga(4)

Answered by Cara S. Maths tutor
4594 Views

Prove that f(x) the inverse function of g(x) where f(x)= - 3x–6 and g(x)= - x/3–2

f(x) and g(x) are inverse functions when the following equations are true:f(g(x))=x
g(f(x))=x

Answered by Sheela K. Maths tutor
2759 Views

We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences